Automated Modeling of Real-Time Implementation - Jensen, Peter Krogsgaard (BRICS Report Series, 1998)
This paper describes ongoing work on the automatic construction of formal models from Real-Time implementations. The model construction is based on measurements of the timed behavior of the threads of an implementation, their causal interaction patterns and external visible events. A specification of the timed behavior is modelled in timed automata and checked against the generated model in order to validate their timed behavior.